Perceptions of waste pickers in an association located in Seridó/RN about the adverse working conditions: An analysis of the collective subject - Dantas, Gerbeson Carlos Batista; Forbeloni, Jacimara Villar; Pacheco, Anderson Sasaki Vasques; Campelo, Ingridy Cardoso; Farias, Henriqueta Monsalisa (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2017)
This paper aims to study the perception of waste pickers, regarding their work conditions, in a recycling association located in the region of Seridó/RN. The study is separated in two parts: firstly, using quantitative data, with extensive and intensive direct observation technique and second, utilizing a qualitative approach, focused in the collective subject discourse and participant observation. To gather the data, a questionnaire was applied with the waste pickers and their daily activities were observed to comprehend the operational process and to accompany the recycle collector activities. It was stated by the interviewees that the main reason to work as waste picker is that they do not want to be unemployed. Regarding their satisfaction, they said that their fulfillment is related with the monthly income. The major problems reported were the low income spared by the association, as well the insalubrity of the activity and preconceptions. With respect their plans, the majority affirmed that need to continue working at the association, then it is possible to affirm that, their future, is conditioned with the possibility of raising their monthly benefit. Finally, although the positive law development and the income shared by the Association, there is a long road to cross in order to create mechanisms to guarantee decent jobs, socioeconomic inclusion and quality of life for them.